Software process improvement initiatives in small and medium firms: A systematic review - Almomani, M.A.T. (Institute of Electrical and Electronics Engineers Inc., 2014)
Nowadays, software firms are playing very important roles in economies all over the world, and majority of these firms are Small and Medium Enterprises (SMEs). The SMEs recognize that it is important to improve their development processes and activities in order to produce software with high quality and to be competitive in the software industry. However, several studies have shown that the SMEs used ad-hoc manner in their development processes and they suffer from lack of the knowledge and resources to do Software Process Improvement (SPI). In this paper, a Systematic Literature Review (SLR) is used to identify and discuss the SPI initiatives in SME software firms. The results of the systematic review showed that the majority of software process improvement initiatives in SME firms are carried out in America and Europe. Only in one Asian country, Hong Kong was the SPI initiative considered and CMM Fast-Track was the model developed. The developed model did not cover all the CMM levels, only levels 1 and 2 were considered. In conclusion, many Software Process Improvement initiatives have been proposed for SME software firms but they have shortcomings such as lack of generalizability and take a lot of time to gain the benefits/advantage of the SPI model after implementation. Â© 2014 IEEE.